2007
DOI: 10.1007/s00464-007-9310-0
|View full text |Cite
|
Sign up to set email alerts
|

Health economic evaluation of therapeutic strategies in patients with idiopathic achalasia: results of a randomized trial comparing pneumatic dilatation with laparoscopic cardiomyotomy

Abstract: The current prospective, controlled clinical trial shows that despite a higher level of clinical efficacy of laparoscopic myotomy to prevent treatment failure in newly diagnosed achalasia, the cost effectiveness of pneumatic dilatation is superior, at least when a reasonable time horizon is applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…By contrast, pneumatic dilation, botulinum toxin injection, and pharmacological treatment are temporary and reversible measures. Moreover, Kostic et al [24] showed that initial treatment cost and total costs were significantly higher for laparoscopic myotomy compared with a pneumatic dilatation-based strategy (P = 0.0002 and P = 0.0019, respectively). However, the cost-effectiveness analysis, relating to the actual treatment failures, revealed that the cost-effectiveness of pneumatic dilatation is superior, at least when a reasonable time horizon is applied.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By contrast, pneumatic dilation, botulinum toxin injection, and pharmacological treatment are temporary and reversible measures. Moreover, Kostic et al [24] showed that initial treatment cost and total costs were significantly higher for laparoscopic myotomy compared with a pneumatic dilatation-based strategy (P = 0.0002 and P = 0.0019, respectively). However, the cost-effectiveness analysis, relating to the actual treatment failures, revealed that the cost-effectiveness of pneumatic dilatation is superior, at least when a reasonable time horizon is applied.…”
Section: Discussionmentioning
confidence: 96%
“…Two randomized studies [23,24] compared the efficacy of pneumatic dilation with laparoscopic myotomy in patients with achalasia. Our meta-analysis showed that there were We used the Jadad scale to assess the quality of trial.…”
Section: Pneumatic Dilation Versus Laparoscopic Myotomymentioning
confidence: 99%
“…Few studies have compared pneumatic dilation (PD) with surgical myotomy, most of them retrospectively and with different techniques (different types of balloons and open vs. laparoscopic myotomy). Some studies have found similar results between both forms of treatment while others have found better results with surgical myotomy in the short and long term …”
Section: Introduction and Aimsmentioning
confidence: 89%
“…Median total direct medical costs of achalasia patients were €2283 in the first year after diagnosis. Previously, costs for pneumatic dilatation and Heller myotomy have been estimated to be approximately €2000 and €7000 respectively . The European Achalasia trial calculated total costs of €3259 for PD and €6720 for Heller .…”
Section: Discussionmentioning
confidence: 99%